Analysis of Students' Mathematical Concept Understanding Ability in Terms of Student Resilience at Ban Kadeng School Thailand - Lubis, Lisa Khairani; Lubis, Ainun Mardiyah; Fitriani, Fitriani; Siregar, Yulia Anita; Jehnah, Abdullah (UNNES JOURNAL, 2024)
Concept understanding ability is one of the main elements in learning mathematics. Understanding students' concept understanding ability will help teachers to plan better learning. Therefore, by understanding students' concepts, understanding ability, and resilience, teachers can improve the quality of education in a school. This study aims to analyze the relationship between students' resilience and understanding of mathematical concepts through story problems. The type of research is qualitative descriptive, the subject of this research is fifth-grade students of Ban Kadeng School, Thailand, and the object of research is the ability to understand students' mathematics concepts in terms of student resilience. The research instruments used are the resilience questionnaire, concept understanding ability test questions, and interviews. The analysis was carried out on indicators of concept understanding, such as restating concepts, classifying objects based on mathematical concepts, and giving examples or counterexamples to the concepts being learned obtained through the instruments that have been carried out. The results showed that in the ability to understand mathematical concepts, Ban Kadeng School students have a moderate level of resilience, namely 65% of students can understand the two main indicators, 25% of students with high resilience can understand all indicators, and 10% of students with low resilience are lacking in understanding the given indicators. So it can be concluded that there are differences in concept understanding ability between high resilience, moderate resilience, and low resilience students in class V Ban Kadeng School, Thailand. The results of this study can be used as a basis for research on the application of learning models, assessments, or types of feedback that are appropriate for students. Kemampuan pemahaaman konsep adalah salah satu unsur utama dalam belajar matematika. Memahami kemampuan pemahaman konsep siswa, akan membantu guru dalam merencanakan pembelajaran yang lebih baik. Oleh sebab itu, dengan memahami kemampuan pemahaman konsep, serta resiliansi siswa, guru akan mampu memperbaiki kualitas pendidikan di suatu sekolah. Penelitian ini bertujuan untuk menganalisis antara resiliensi siswa dan pemahaman konsep matematis melalui penggunaan soal cerita. Jenis penelitian deskriftif kualitatif, subjek penelitian ini adalah siswa kelas V BanKadeng School, Thailand, dan objek penelitiannya adalah kemampuan pemahaman konsep Matematika siswa ditinjau dari resiliennsi siswa. Instrumen penelitian yang digunakan adalah angket resiliensi, soal tes kemampuan pemahaman konsep dan wawancara. Analisis dilakukan terhadap indikator pemahaman konsep, seperti menyatakan ulang konsep, mengklasifikasikan objek berdasarkan konsep matematika, dan memberikan contoh atau kontra contoh pada konsep yang dipelajari yang diperoleh melalui instrumen yang telah dilakukan. Hasil penelitian menunjukkan dalam kemampuan pemahaman konsep matematis siswa Ban Kadeng School memiliki tingkat resiliensi sedang yaitu sebanyak 65% siswa dapat mememahami dua indikator utama, siswa dengan resiliensi tinggi sebanyak 25% dapat memahami keseluruhan indikator, dan siswa dengan resiliensi rendah sebanyak 10% kurang dalam memahami indikator yang diberikan. Jadi dapat disimpulkan bahwa terdapat perbedaan kemampuan pemahaman konsep antara siswa resiliensi tinggi, resiliensi sedang, dan resiliensi rendah di kelas V Ban Kadeng School, Thailand. Hasil penelitian ini dapat digunakan sebagai dasar untuk riset tentang penerapan model pembelajaran, asesmen, ataupun jenis feedback yang tepat untuk siswa.